2021
DOI: 10.3390/ijerph182413108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sampietrini Pavers on Urban Heat Islands

Abstract: Cool pavements are reflective and/or permeable pavements that improve microclimate of urban areas where heat islands cause discomfort to citizens. Stone pavements lower surface temperatures and reduce the amount of heat absorbed. This study assessed, using ENVI-met 4.3 LITE software, how air temperature and predicted mean vote depend on physical properties of the road pavement. A comparative microclimatic analysis was implemented on a rectangular square in Rome (Italy) in the summer, paved in three different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The originality of the study lies in focusing on the role of emissivity in building façades with relation to effects on outdoor comfort conditions, which is generally investigated by paying more attention to horizontal surfaces, namely roofs [97,98] and paved spaces [99]. The main focus of the scientific literature is usually on the specific albedo of materials [100], on the analysis of UHI patterns and intensities with relation to urban typologies [101], and on mitigation techniques and technologies [102], while the role of vertical surfaces is basically addressed to explore cool façade optimization [103].…”
Section: Scope Of the Researchmentioning
confidence: 99%
“…The originality of the study lies in focusing on the role of emissivity in building façades with relation to effects on outdoor comfort conditions, which is generally investigated by paying more attention to horizontal surfaces, namely roofs [97,98] and paved spaces [99]. The main focus of the scientific literature is usually on the specific albedo of materials [100], on the analysis of UHI patterns and intensities with relation to urban typologies [101], and on mitigation techniques and technologies [102], while the role of vertical surfaces is basically addressed to explore cool façade optimization [103].…”
Section: Scope Of the Researchmentioning
confidence: 99%
“…Indeed, stone surfaced roads were mostly used in towns, while long distance roads were mainly surfaced with gravel. Paved roads sometimes used rectangular stones and sometimes used close fitting polygonal stones, often eight sided, and it is possible that Romans were already debating regarding relative structural advantage of different shapes in paves (Sitwell, 1981;Zoccali et al, 2018;Garilli & Giuliani, 2018;Soutsos et al, 2011;Moretti et al, 2021). Many Roman roads today have ruts that we can assume were dug during the construction of the roads to guide the chariot wheels, especially on steep roads, and then the repeated wheeling (vehicles could weigh up to 750 kg per axle) only increased their size.…”
Section: Introductionmentioning
confidence: 99%
“…Cotana et al [26] reported a reduction of 16,000 tons of CO 2eq provided by a high-albedo surface area of 115,000 m 2 for a service life of 30 years. In addition, permeable pavements are more effective than traditional ones in reducing air temperature compared to the current asphalt surface [27].…”
Section: Introductionmentioning
confidence: 99%